2022
DOI: 10.1093/eurheartj/ehac544.654
|View full text |Cite
|
Sign up to set email alerts
|

Importance of bilateral vagus nerve stimulation for effective atrioventricular node denervation during cardioneuroablation

Abstract: Background The progression of parasympathetic denervation of the atrioventricular node (AVN) during cardioneuroablation (CNA) can be evaluated by extracardiac vagal stimulation (ECVS). The right vagus nerve is usually used for stimulation (R-ECVS) because the right jugular vein is easily accessible. However, the AVN node is predominantly under the control of the left vagus nerve. Purpose To highlight the importance of left va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The post-ablation absence of provoked vagal responses of sinus and AV nodes is a highly sensitive and specific measure of their denervation. 12 However, the utility of extracardiac vagus nerve stimulation for guiding the CNA has not been formally investigated in CNA studies with clinical endpoints.…”
Section: Additional Controversial Issues (Gap In Knowledge)mentioning
confidence: 99%
“…The post-ablation absence of provoked vagal responses of sinus and AV nodes is a highly sensitive and specific measure of their denervation. 12 However, the utility of extracardiac vagus nerve stimulation for guiding the CNA has not been formally investigated in CNA studies with clinical endpoints.…”
Section: Additional Controversial Issues (Gap In Knowledge)mentioning
confidence: 99%
“…Although standalone ablation of the superior right ganglionated plexus (GP) (SRGP) has a significant impact on the AV node, complete AV nodal denervation in many patients is only achievable by additional ablation of the posteromedial left GP (PMLGP). 2 Nevertheless, SRGP ablation alone can be clinically successful, even with ablation limited to the right atrial aspect of the superior interatrial septum, as we demonstrated previously. 3 …”
mentioning
confidence: 59%
“…Our experience suggests that there may be a difference between the right and left vagal nerve input. 26,27 Therefore, it is important stimulating vagal nerves on both sides to ensure complete vagal denervation.…”
mentioning
confidence: 99%
“…The procedure has to be performed in general anesthesia since high frequency stimulation is painful and results in muscular contractions. Our experience suggests that there may be a difference between the right and left vagal nerve input 26,27 . Therefore, it is important stimulating vagal nerves on both sides to ensure complete vagal denervation.…”
mentioning
confidence: 99%